Secondary Outcomes of the Ole e 1 Proteins Involved in Pollen Tube Development: Impact on Allergies - Fernández-González, M.; González-Fernández, E.; Fernández-González, D.; Rodríguez-Rajo, F. Javier (Frontiers in Plant Science, 2020)
The Ole e 1 protein is involved in the olive fertilization mechanism controlling the pollen tube development. Similarly to the process by which pollen grains hydrated and form a pollen tube at their arrival to the female gametophyte, when pollen grains fall in the nasal mucosa the expression of the Ole e 1 induce allergic reaction in sensitive individuals. The research was conducted in Ourense (North-western Spain), during the 2009-2018 period. The Ole e 1 protein was collected by a Cyclone Sampler and processed with ELISA methodology. The airborne Olea pollen was monitored with a Hirst type volumetric sampler. Allergy risk episodes identified by pollen concentrations were detected in 5 of the 10 studied years, all with moderate risk. Considering the pollen and Ole e 1 concentrations together to ascertain the real risk episodes, increased to 9 the years with moderate risk episodes and 3 years with high risk episodes. Some years of low annual pollen concentrations registered high total Ole e 1 amounts. The tree increases the Ole e 1 synthesis in years with lower pollen production to ensure an appropriate pollen tube elongation for a successful fertilization. This fact could justify higher sensitization rates in years with lower expected pollen. The present method contributes to the determination of the real exposure to Ole e 1 allergen evaluating the role of this protein as an aeroallergen for sensitized population. In the future should be considered to enhance the prevention of pollinosis clinical symptomatology and the reduction of medicine consumption.